Group of teenage girls at a swimming hole - Unknown:::Creator::::::::::::
Photograph shows a group of teenage girls at a swimming hole. Some of the group are in the water and some are still on the bank. They are in a forested area which is probably at the YWCA's Camp Ayun Mapu in Big Basin, California